2010
DOI: 10.1038/cr.2010.4
|View full text |Cite
|
Sign up to set email alerts
|

ATF4 regulates lipid metabolism and thermogenesis

Abstract: Activating transcription factor 4 (ATF4) has been shown to play key roles in many physiological processes. There are no reports, however, demonstrating a direct link between ATF4 and lipid metabolism. We noticed that Atf4-deficient mice are lean, suggesting a possible role for ATF4 in regulating lipid metabolism. The goal of our current study is to investigate the involvement of ATF4 in lipid metabolism and elucidate the underlying mechanisms. Studies using Atf4-deficient mice revealed increased energy expendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
102
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(113 citation statements)
references
References 44 publications
9
102
0
2
Order By: Relevance
“…In addition, these patients present defects in metabolic pathways including lipid metabolism where ATF4 was shown to play an important role (55,56). Studies in ATF4-deficient mice have shown that the ATF4 transcriptional program may affect lipolysis and expression of lipogenic genes (57). Moreover, it was previously reported that mice with enforced expression of an active C-terminal fragment of GADD34 to attenuate eIF2α phosphorylation have decreased expression of key hepatic transcriptional regulators of intermediary metabolism including PPARγ (58).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these patients present defects in metabolic pathways including lipid metabolism where ATF4 was shown to play an important role (55,56). Studies in ATF4-deficient mice have shown that the ATF4 transcriptional program may affect lipolysis and expression of lipogenic genes (57). Moreover, it was previously reported that mice with enforced expression of an active C-terminal fragment of GADD34 to attenuate eIF2α phosphorylation have decreased expression of key hepatic transcriptional regulators of intermediary metabolism including PPARγ (58).…”
Section: Discussionmentioning
confidence: 99%
“…ATF4 depletion seems to enhance insulin sensitivity in the liver (26). The improvement in glucose homeostasis along with enhanced hepatic insulin sensitivity contributes to improved lipid metabolism in Atf4 Ϫ/Ϫ mice (23,25). As an alternative mechanism, ATF4 exerts a direct effect on hepatic lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…ATF4 deficiency also stimulates lipolysis in adipose tissue, contributing to increased energy expenditure in Atf4 Ϫ/Ϫ mice (23). Atf4 Ϫ/Ϫ mice are lean, due to reduced fat mass (22,23). This effect protects against the development of glucose intolerance and insulin resistance in Atf4 Ϫ/Ϫ mice in response to high fat feeding (24,25).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study in Guo's laboratory has led to the identification of a novel function for ATF4 in regulating lipid metabolism, thermogenesis, and glucose metabolism [47,48]. Atf4-deficient mice were found to be lean and exhibit increased energy expenditure due to increased thermogenesis in BAT, as described by Seo et al [44], as well as increased lipolysis and decreased lipogenesis in WAT [47].…”
Section: Atf4mentioning
confidence: 99%